Pretty little secrets - Shepard, Sara, 1977- (Shepard, Sara, 1977- Pretty little liars., 2011)
Rule number one of being an effective stalker: get to know your prey, the trouble they get into, the messes they make, and the secrets they keep. Hanna's desperate for a very personal session with her gym trainer. Emily is number one on Santa's naughty list. Aria's old flame from Iceland is about to land her in hot water. And Spencer's resorting to some backhanded tactics to get what she wants.